PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN IMPLEMENTASI PERENCANAAN STRATEGI TERHADAP MUTU PENIDIDKAN DI SD NEGERI SEKECAMATAN GANDUS - Febriana Kusmilawati; Bukman Lian; Djunaidi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine and analyze (1) The influence of principal leadership on the quality of education in Public Elementary Schools in Gandus District, Palembang City (2) the influence of the implementation of strategic planning in improving the quality of education in Public Elementary Schools in Gandus District, Palembang City. (3). the influence of principal leadership and implementation of strategic planning on improving the quality of education in Public Elementary Schools in Gandus District, Palembang City. This study is a descriptive method study with a quantitative approach. This study was conducted at Public Elementary Schools in Gandus District, Palembang City, with a sample in this study of 107 teachers at Public Elementary Schools in Gandus District, Palembang City. Data collection techniques used questionnaires and documentation. The validity test used construct validity, while the reliability test used Cronbach's Alpha. The prerequisite analysis test used the normality test, Heteroscedasticity Test, and Multicollinearity Test, and the data was analyzed using multiple linear regression techniques, correlation, t-test and F-test. The results of the study show that: (1) The principal's leadership has an effect on the quality of education at the Gandus District Public Elementary School, Palembang City. (2) The implementation of strategic planning has an effect on improving the quality of education at the Gandus District Public Elementary School, Palembang City. (3). The principal's leadership and the implementation of strategic planning simultaneously have an effect on improving the quality of education at the Gandus District Public Elementary School, Palembang City.